9 bit superconductive single‐flux‐quantum digital‐to‐analogue converter. Issue 22 (1st October 2014) - Mizugaki, Y.; Takahashi, Y.; Shimada, H.; Maezawa, M.
Abstract : The design and operation of a 9 bit superconductive single‐flux‐quantum (SFQ) digital‐to‐analogue converter (DAC) are presented. The DAC comprises a 9 bit variable SFQ pulse number multiplier and a 100‐fold voltage multiplier. An SFQ pulse‐frequency modulation technique is employed for coding the analogue output voltage. The DAC is fabricated using an Nb Josephson integration technology. Its output voltage waveform, the amplitude of which is up to 2.54 m V pp, is controlled by digital input signals from a room‐temperature data generator.